Graphene nanopetal wire supercapacitors with high energy density and thermal durability. (August 2017) - Xiong, Guoping; He, Pingge; Huang, Boyun; Chen, Tengfei; Bo, Zheng; Fisher, Timothy S.
Abstract: Wire supercapacitors have recently elicited attention due to their potential to be woven into textiles as flexible power supplies for wearable electronic devices. However, contemporary wire supercapacitors generally suffer from low energy density and complicated fabrication and assembly processes. Here, we report a unique design of asymmetric wire supercapacitors in a wrap-twist architecture, with graphene nanopetals grown on carbon fiber tow as negative electrodes and MnO2 nanosheets electrodeposited on carbon nanotube paper as positive electrodes. The wrap-twist structure integrates both positive and negative electrodes with edge-enriched nanostructures, and a new assembly procedure greatly increases the contact area between the two electrodes, leading to significantly improved electrochemical performance. Such asymmetric wire supercapacitors exhibit ultrahigh capacitances of over 40 mF cm −1, outstanding energy and power densities, with energy densities up to 12 µW h cm −1 (approx. 50 µW h cm −2 on an area basis) and power densities up to approx. 3.7 mW cm −1 (approx. 15.4 mW cm −2 ), good cyclic stability and excellent flexibility. Moreover, the thermal performance of such wire supercapacitors is assessed by characterizing temperature effects on electrochemical performance over a temperature window ranging from 2 to 80 °C. The outstanding electrochemical and thermal performance of the wire supercapacitors demonstrates their promising potential as flexible power sources for wearable electronic devices. Graphical abstract: Highlights: A design of asymmetric wire supercapacitors in a wrap-twist architecture. Edge-enriched nanostructures (MnO2 nanosheets and graphene nanopetals) as electrodes. Wire supercapacitors exhibiting outstanding electrochemical performance, high mechanical robustness and high flexibility. A deep understanding of thermal behavior of wire supercapacitors.